1984
DOI: 10.1029/ja089ia04p02217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energetic heavy ions on electromagnetic ion cyclotron wave generation in the plasmapause region

Abstract: An expression for the linear electromagnetic ion cyclotron convective growth rate has been derived, considering multiple ions in the energetic anisotropic component of the plasma (which provides the free energy for the instability) as well as in the cold component of the plasma. This represents a modification of recent treatments investigating electromagnetic ion cyclotron growth rates which have considered only hydrogen ions in the energetic component. Four major effects on the growth and propagation characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
295
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(318 citation statements)
references
References 46 publications
12
295
1
1
Order By: Relevance
“…Cold plasma density is expected to increase during storm recovery phase as a result of plasmasphere refilling. However, an increase in plasma density shifts the growth rate peak to a lower frequency [Kozyra et al, 1984], excluding the change in cold plasma density as an explanation for the observed increase of structured Pc1 frequency.…”
Section: Jordanova Et Al [1997] Discussed Two Mechanismsmentioning
confidence: 89%
“…Cold plasma density is expected to increase during storm recovery phase as a result of plasmasphere refilling. However, an increase in plasma density shifts the growth rate peak to a lower frequency [Kozyra et al, 1984], excluding the change in cold plasma density as an explanation for the observed increase of structured Pc1 frequency.…”
Section: Jordanova Et Al [1997] Discussed Two Mechanismsmentioning
confidence: 89%
“…A variety of modes is possible, in principle. One of the main lines of distinction is whether the waves are dominated by a single ion species (Brinca et al, 1990;Chaston et al, 1994Chaston et al, , 1999 or interplay of multiple ion components should be invoked (Smith and Brice, 1964;Young et al, 1981;Gomberoff and Neira, 1983;Kozyra et al, 1984;Brinca et al, 1989). Based on wave data only, we shall have to question both hypotheses.…”
Section: Wave Properties -Discussionmentioning
confidence: 99%
“…Simulation work on ion instabilities possible under magnetotail conditions has been reported by Gary and Winske (1990), Gary et al (1993, Gary and Lee (1994). Because of the multi-ion character of the plasmas in the inner magnetosphere and the near-Earth magnetotail, the dispersion in the low frequency range of multi-ion plasmas has also received considerable attention in works by Smith and Brice (1964), Young et al (1981), Gomberoff and Neira (1983), Kozyra et al (1984), Chaston et al (1997). Ion cyclotron heating of heavy ions by ion waves has been discussed by Chaston et al (2000).…”
Section: Chastonmentioning
confidence: 99%
“…However, helium ions may also play an important role. Although helium is probably not present in significant enough quantities to drive the wave growth, small quantities of helium ions can introduce stop bands in the frequency spectrum driven by hydrogen ions [Kozyra et al, 1984]. These stop bands are located at 0.25 DH+ and can change the EMIC mode wave spectra, influencing the energies of relativistic electrons precipitated.…”
Section: Growth Of Electromagnetic Ion Cyclotron Mode Wavesmentioning
confidence: 99%